2009
DOI: 10.1158/1078-0432.ccr-08-1305
|View full text |Cite
|
Sign up to set email alerts
|

Obstructing Shedding of the Immunostimulatory MHC Class I Chain–Related Gene B Prevents Tumor Formation

Abstract: Purpose: Clinical observations have suggested that shedding of the MHC class I chain^related molecule (MIC) may be one of the mechanisms by which tumors evade host immunosurveillance and progress. However, this hypothesis has never been proven. In this study, we tested this hypothesis using a prostate tumor model and investigated the effect of shedding of MIC on tumor development. Experimental Design: We generated a shedding-resistant noncleavable form of MICB (MICB.A2).We overexpressed MICB.A2, the wild-type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
54
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 39 publications
4
54
0
Order By: Relevance
“…The shedding of NKG2D ligands has been frequently observed in most tumors, and leads to downregulation of NKG2D on NK cells and reduced NK cell cytotoxicity. 32,44,45 It has also been found that downregulation of B7-H6 (a ligand for the activating receptor NKp30) on various tumor cell lines or release of BAG6/BTA3 (a soluble ligand for NKp30) from chronic lymphocytic leukemia cells reduces the NKp30-dependent effector functions of NK cells. 20 Suppressive cytokines (such as transforming growth factor (TGF)-b and IL-10) and regulatory T (Treg) cells within tumor microenvironments have been shown to suppress NKG2D and NKp30 expression on NK or CD8 1 T cells and also reduce MICA and ULBP expression on malignant cells.…”
Section: Nk Receptors In Tumorsmentioning
confidence: 99%
“…The shedding of NKG2D ligands has been frequently observed in most tumors, and leads to downregulation of NKG2D on NK cells and reduced NK cell cytotoxicity. 32,44,45 It has also been found that downregulation of B7-H6 (a ligand for the activating receptor NKp30) on various tumor cell lines or release of BAG6/BTA3 (a soluble ligand for NKp30) from chronic lymphocytic leukemia cells reduces the NKp30-dependent effector functions of NK cells. 20 Suppressive cytokines (such as transforming growth factor (TGF)-b and IL-10) and regulatory T (Treg) cells within tumor microenvironments have been shown to suppress NKG2D and NKp30 expression on NK or CD8 1 T cells and also reduce MICA and ULBP expression on malignant cells.…”
Section: Nk Receptors In Tumorsmentioning
confidence: 99%
“…No homolog of human MIC has yet been described in mice. In general, human or mouse NKG2D does not recognize the ligands of their counterparts, except that mouse NKG2D can recognize human MICB and selective alleles of human MICA (32)(33)(34). Most importantly, tumor shedding of NKG2D ligands to downregulate NKG2D function has been described and proposed as one of the immune evasion mechanisms in human cancer, but has not been described in mice.…”
Section: Introductionmentioning
confidence: 99%
“…To clarify the impact of human NKG2D ligands on cancer, we exploited the knowledge that the human NKG2D ligand MICB can stimulate mouse NKG2D immunity (33,34) and generated 2 unique lines of "humanized" bi-transgenic (bi-Tg) mouse models, TRAMP/MICB and TRAMP/MICB.A2. The former expresses the native human MICB, which can be shed by tumor cells, while the latter expresses an engineered membrane-restricted MICB (designated as MICB.A2) in the prostate of the autochthonous TRAMP mouse (33,35,36). Using these models, for what we believe is the first time, we conclusively demonstrate the distinct roles of membrane-bound NKG2D ligands and tumor-derived soluble NKG2D ligands on cancer progression.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from reducing NKG2D-L expression on the tumor cell surface, the release of soluble molecules may also impair immune surveillance by promoting down-regulation of NKG2D (12,13). In fact, the sustained presence in vivo of NKG2D-L down-modulates the receptor (14,15), and, at least in mouse models, blocking shedding of NKG2D-L can prevent tumor formation (16). In patients with colorectal or prostate cancer, hepatocellular carcinoma, and neuroblastoma, decreased NKG2D expression and impaired activation of NK cells was associated with high levels of soluble MICA in serum (17)(18)(19)(20).…”
mentioning
confidence: 99%